Case report: Nephrotic syndrome and portal hypertensive ascites after allogeneic hematopoietic stem cell transplantation: a rare manifestation of chronic graft-versus-host disease - Ai, SanXi; Wen, YuBing; Fan, XiaoHong; Hua, TianRui; Ye, Wei; Li, XueMei; Qin, Yan (Frontiers in Immunology, 2024)
Chronic graft-versus-host disease (GVHD) is a major complication after allogeneic hematopoietic stem cell transplantation (HSCT). Chronic GVHD may have atypical manifestations affecting non-classical organs. The diagnosis in patients with atypical manifestations of chronic GVHD is particullarly challenging, and there is a lack of knowledge regarding their pathogenesis and treatment. We reported a case who developed post-HSCT nephrotic syndrome and portal hypertensive ascites, which are both rare and atypical manifestations of chronic GVHD. Kidney biopsy revealed membranous nephropathy and renal thrombotic microangiography with glomerular immune deposits, suggesting antibody-mediated kidney injury. Treatment with ruxolitinib resulted in remission of both nephrotic syndrome and ascites, suggesting a role of cytokines in the pathogenesis. This case highlighted the awareness of nephrotic syndrome and portal hypertensive ascites as atypical manifestations of chronic GVHD, and the efficacy of ruxolitinib for the two manifestations.